Спектрально-когерентні характеристики електроенцефалограми в осіб із різною швидкістю обробки інформації вищими відділами центральної нервової системи - Юхименко, Лілія; Yukhimenko, Lilia (Східноєвропейський національний університет імені Лесі Українки, 2016)
Досліджено особливості електричної активності головного мозку (ЕЕГ) та швидкість центральної обробки інформації (ШЦОІ). Установлено статистично значимі різниці потужності та когерентності (Ког) ЕЕГ у групах обстежуваних із різною ШЦОІ. Установлено зв’язок між характеристикамиШЦОІ й ЕЕГ. The features of electrical activity of the brain (EEG) and the speed of central information processing (CIP) were studied. Statistically significant differences of capacity and coherence (Coh) of EEG were found in the groups of the examined persons with different CIP. The persons with high CIP were characterized with higher capacity and Coh in the concerned areas of the cerebral cortex if compared with the persons with its middle and low levels. Correlation analysis confirmed the accuracy of the links between the characteristics of CIP and EEG. The differences in intra- and inter-hemispheric spectral-coherent dynamics of EEG characteristics were found during processing and differentiating stimuli in the examined persons depending on the PIC. We consider that the changes in the level and structure of the spectral-coherent linkages of и, б and в-range potentials of EEG can be neurophysiologic correlates of information processing speed by higher parts of the central nervous system.
Spectral and Coherent Characteristics of Electroencephalogram in Persons with Different Speed of Information Processing by Higher Parts of Central Nervous System.
Keywords: електроенцефалографія; потужність та когерентність ЕЕГ; швидкість центральної обробки інформації; electroencephalography; EEG capacity and coherence; central information processing speed